High throughput DNA sequencing with a microfabricated 96-lane capillary array electrophoresis bioprocessor - Paegel, Brian M. (The National Academy of Sciences, 2002)
High throughput DNA sequencing has been performed by using a microfabricated 96-channel radial capillary array electrophoresis (μCAE) microchannel plate detected by a 4-color rotary confocal fluorescence scanner. The microchannel plate features a novel injector for uniform sieving matrix loading as well as high resolution, tapered turns that provide an effective separation length of 15.9 cm on a compact 150-mm diameter wafer. Expanded common buffer chambers for the cathode, anode, and waste reservoirs are used to simplify electrode addressing and to counteract buffering capacity depletion arising from the high electrophoretic current. DNA sequencing data from 95 successful lanes out of 96 lanes run in parallel were batch-processed with basefinder, producing an average read length of 430 bp (phred q ≥ 20). Phred quality values were found to exceed 40 (0.01% probability of incorrectly calling a base) for over 80% of the read length. The μCAE system demonstrated here produces sequencing data at a rate of 1.7 kbp/min, a 5-fold increase over current commercial capillary array electrophoresis technology. Additionally, this system permits lower reagent volumes and lower sample concentrations, and it presents numerous possibilities for integrated sample preparation and handling. The unique capabilities of μCAE technology should make it the next generation, high performance DNA sequencing platform.